SISTEMAS QUIMILUMINESCENTES COM PEROXIDASE (EC:1.11.1.7) E SUAS APLICACOES EM ANALISES CLINICAS - Brunetti, Iguatemy Lourenço [UNESP]; De Faria-Oliveira, O. M M [UNESP] (My University, 1995)
The enzyme horseradish peroxidase HRP (EC:1.11.1.7), has both acid and basic isoenzymes, catalyses a wide range of reactions (acting as an oxiredutase or an oxidase) and is thought capable of one- or two-electrons oxidations depending on the substrate employed. Today, the methodology for these assay can be chemiluminescent reactions and enhanced chemiluminescent. The enhanced chemiluminescent assay with system HRP, luminol, peroxide and an enhancer has provided the basis for a convenient and sensitive assay for peroxidase and peroxidase conjugates, DNA probe and blotting assay. It is particularly more advantageous than the others, because is very rapid, more sensitive (attomoles), easy to do and technically simple, and is relatively specific for HRP (reduces the effect of the interference).
Chemiluminescence systems with peroxidase (EC:1.11.1.7) and its applications in clinical analysis
Keywords: chemiluminescence; enhanced chemiluminescence; enzymes; luminol; peroxidase; horseradish peroxidase; peroxide; chemoluminescence; enzyme analysis; enzyme assay; review